BENTUK KELEMBAGAAN DAN POLA PEMBIAYAAN LAND BANKING PUBLIK DI INDONESIA - Azhari Pamungkas; Haryo Winarso (TATALOKA, 2018)
The application of land banking is likely to be conducted in Indonesia as well as its success in various countries in solving various land-related problems. This study aims to formulate an institutional set up and funding scheme for land banking in Indonesia. This study utilized an adoption of Delphi method to compile and interprete expert opinions, in addition extensive review of literature and legislations were also conducted. This study recommends the set up of public owned land banking company that consist of main company and subsidiary company. The main company is 100% owned by the government. The subsidiary company is jointly developed with private sector and community. The main company is assigned to bank land for public purposes (eg. infrastructures, public housing, facilities) and not for profit. The subsidiary company is assigned to bank land for development and giving opportunity the land owners to get share and profit. The set up land bank company is funded by local budget. Profit from the subsidiary company can be reinvented to the main company.